Sustainable public awareness on solid waste management and environmental care using logistics regression - Farida Zulkipli; Nurul Husna Jamian; Sulkily Mohd Nopiah; Noor Ezlin Ahmad Basri; Cheng, Jack Kie (Penerbit Universiti Kebangsaan Malaysia, 2022)
Solid waste management and environmental care are essential in all countries to ensure sustainability at all times. But awareness on the importance of both is not yet satisfactory. This is evidenced by the increasing amounts of solid waste generated and the lack of oversight due to public community involvement. The purpose of this study is to investigate the sustainability of public awareness on solid waste management and environmental care among the population of Malaysia. This study uses an online questionnaire for the data collection process. The logistic regression method is used to analyze the data. A total of 422 respondents represented by 20.9% were male while 79.1% were female. The results showed that only 37.91% of respondents were aware of solid waste management and concern for the environment. In fact, more than 50% of respondents are still less aware of solid waste management and environmental concerns. This shows that most of the communities in Malaysia had a lack awareness on the importance of waste management and environmental care. The culture and values of individual responsibility play an important role in ensuring that environmental sustainability is maintained. Solid waste management and environmental care coalitions need to have broad coverage across the country so that all communities are aware and understand the shared responsibility for waste management and environmental care. This awareness will help achieve the national agenda through Joint Prosperity as well as the Sustainable Development Goals by 2030.